Новый вид паразитической копеподы Salmincola mica sp. n. (Lernaeopodidae) c обыкновенного валька, Prosopium cylindraceum (Coregonidae), из реки Анадырь - Шедько, М.Б. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
При обследовании сиговых рыб из р. Анадырь (п-ов Чукотка) на жаберных лепестках обыкновенного валька, Prosopium cylindraceum, найдены копеподы Salmincola mica sp. n. Диагноз — максиллы II утолщены вокруг основания длинной булавовидной буллы; вентральный отросток 4-го дистального членика эндоподита антенны II равен по размерам спинному крюку 1, вооружен шипиками и имеет у основания маленький отросток 5; длина соска максиллепед менее 1/3 длины рукоятки субхелы; мандибула с 7 зубами, из которых 3 проксимальных — наиболее мелкие; максилла I с редуцированной вентральной папиллой. Приводится описание найденного вида копепод, сопровождаемое рисунками. At inspection of the coregonid fishes from the Anadyr River (Chukchi Peninsula) two females (mature adult and young adult) of the new species Salmincola mica sp. n., were found on the tip of the gill filaments of round whitefish Prosopium cylindraceum. The diagnosis of S. mica sp. n.: second maxilla has a marked inflation around of the basis bulla, wiсh is clavate, long; length of maxilliped palp is less than 1/3 length of subchela (exclusive of claw); ventral process 4 of terminal segment of endopod of second antenna is as large as dorsal hook 1 and armed with relatively large spines, also it has another much smaller process 5; the ventral papilla of the first maxilla is reduced, exopod has short seta; the mandible has seven teeth, the proximal three being much smaller than the rest. The description of the found copepods is resulted.